KOMUNIKASI DAN KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASI DI PT. BINA SAN PRIMA AREA JAWA BARAT - Triskawati Triskawati; Ani Yunaningsih (Magister Manajemen Pascasarjana Universitas Langlangbuana, 2020)
This study focuses on the Communication, Leadership and Organizational Commitment. This study aims to identify and analyze: The first, an overview of Communication, Leadership, and Organizational Commitment at PT. Bina San Prima West Java area; Second, the influence of Communication to Organizational Commitment; third, the influence of Leadership to Organizational Commitment; fourth, Communication and Leadership influences the Organizational Commitment . The sample in this study is sales force of PT. Bina San Prima West Java Area with branches are Bandung 1 (Bandung PW), Bandung 2 (Bandung LG), Kerawang dan Bekasi. To determine the influence between variables, the analysis used is Path Analysis. This study concluded that Communication influence to the Organizational Commitment, Leadership influence to the Organizational Commitment, Communication and Leadership influence on Organizational Commitment.